Honor and political violence: Micro-level findings from a survey in Thailand. (November 2017) - Bjarnegård, Elin; Brounéus, Karen; Melander, Erik
Who participates in political violence? In this study, we investigate the issue at the micro-level, comparing individuals who have used violence in political uprisings with those who have not. We develop our argument from the observation that men are strongly overrepresented in political violence, although most men do not participate. Literature on masculinities emphasizes the role of honor and its links to different forms of violence, such as domestic abuse, criminal violence, and violent attitudes. Building on this literature, we discern two separate but related aspects of honor: honor as male societal privilege and control over female sexuality, that is, patriarchal values, and honor as ideals of masculine toughness, that is, the perceived necessity for men to be fierce and respond to affronts with violence or threats of violence in order to preserve status. We argue that patriarchal values combined with ideals of masculine toughness together constitute honor ideology, which contributes in turn to the explanation of who participates in political violence. We present new and unique individual-level survey data on these issues, collected in Thailand. We find that honor ideology strongly and robustly predicts a higher likelihood of participating in political violence among male political activists. A number of previous studies found a macro-level relationship between gender equality and peacefulness in a society. This study provides evidence for one micro-level mechanism linking gender equality and political violence at the macro level. Based on these results, we conclude that honor ideology endorsement is a driver of violence in political conflicts.